Benchmarking Data Science: 12 Ways to Lie With Statistics and Performance on Parallel Computers. (Computer (00189162), 2022)
We humorously discuss 12 fallacies when focusing on compute performance that we have frequently observed in practice. We follow each with a recommendation to mitigate the danger and hope to contribute to good benchmarking etiquette for data science.